Lessons from Deregulation: Telecommunications and Airlines after the Crunch - Kahn, Alfred E., (Rowman & Littlefield Publishers, 2003)
Over the last several years, the value of stocks in both the airline and the telecommunications industries have dropped catastrophically. Since these industries were among the most importantand most visibleto have been unleashed from regulation in recent decades (albeit in widely differing degree), their difficulties have raised the question of whether their deregulation should be reconsidered or even reversed. Alfred E. Kahn, one of the foremost authorities on deregulation, argues in this book that every passing year demonstrates the superiority of the road chosen for the airlines. He contrasts the financial meltdowns of both the airline and telecommunications industries with others taking place at the same time, particularly in technology-related stocks and "dot.coms," pointing out that these sectors were also relatively free of direct economic regulation. Their experience provides a useful counter to the natural tendency to blame all the woes of aviation and telecommunications on government policy. This book provides a valuable and accessible guide to unraveling the complex world of network deregulation. It will serve as a reference point for practioners and policymakers, as well as an important introduction for the general public.